Tinjauan Karakteristik Sumber Daya Manusia Di Unit Rekam Medis Dalam Meningkatkan Efisiensi Dan Efektivitas Pelayanan Di UPT Puskesmas Kedai Durian Tahun 2022 - Melati Hutauruk, Puput; Ritonga, Abdul Malik; Nazara, Yasrius (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
To manage a medical records unit and produce quality health information, adequate resource support is needed, including human resources, facilities and infrastructure. The aim of this research is to determine the management of human resources in the medical records unit in improving the efficiency and effectiveness of services at the UPT Puskesmas Kedai Durian. This research uses a descriptive qualitative research type with a cross sectional approach where data collection was carried out by interviews in September 2022 with employees of the medical records unit at the Toko Durian Health Center, Medan City with the number of officers in the medical records unit being 4 people, including 1 D3 medical records person, 1 person D3 nursing, 1 person D4 midwifery, and 1 person S1 nursing. Based on research results, in managing human resources in the medical records unit to improve the efficiency and effectiveness of services at the UPT Puskesmas Kedai Durian, the majority of employees in the medical records unit do not have a medical records background and have never attended previous training. In conclusion, the UPT of the Kedai Durian Health Center in Medan City is still not efficient and effective in providing services in the Medical Records Unit.